A Brief Measure of Unbearable Psychache. Issue 6 (10th May 2019) - Pachkowski, Mikayla C.; May, Alexis M.; Tsai, Michelle; Klonsky, E. David
Abstract : Objective: Psychache has been proposed to cause suicide when it becomes unbearable. However, existing measures of psychache do not directly target unbearable psychache. Thus, the purpose of the current study was to provide initial validation for a brief measure of unbearable psychache. Method: Three items were selected to create the Unbearable Psychache Scale (UP3). Psychometric properties were assessed in two populations: (1) an online sample composed of 1, 006 adults (53% male) from various locations in the United States and (2) a sample of 190 psychiatric inpatient adults (47% male) from a hospital in Western Canada. Results: In both samples, the UP3 demonstrated excellent internal reliability, and strong convergent and predictive validity. Additionally, the UP3 predicted significant variance in suicidal ideation over and above documented correlates of suicidal ideation including general psychache, hopelessness, perceived burdensomeness, and low belongingness. Conclusions: The UP3 is a brief, psychometrically sound measure of unbearable psychache that may be well‐suited for use in research protocols and clinical assessments.